Legal Politics of Weakening The Corruption Eradication Commission - Muhammad Nur Vivananda Irsyad, Sena kogam (Jurnal Cakrawala Hukum, 2025)
Corruption is one of the criminal crimes that requires special legal attention in Indonesia. This phenomenon makes legal source references the most crucial instrument to maintain the stability of legal politicization in state institutions, especially the Corruption Eradication Commission. This study analyzes the changes to the corruption eradication law that were released in 2019. There are indications that the results of the legal reform contain values that weaken the enforcement carried out by the Corruption Eradication Commission. Based on this research gap, the author uses the bibliometric analysis method based on a literature review. This method has three components, namely network, density, and overlay visualization, to continue the analysis using legal logic. To focus on the research topic, the author formulates a research question, namely, why does the renewal of the corruption eradication law released in 2019 contain values that weaken the previous law, namely, 2002? The results found were that the impact of the author’s hypothesis was proven by the weakening of the Indonesian government regarding the handling of corruption cases in Indonesia and the negative impacts related to views or bilateral relations with other countries.